2018
DOI: 10.1038/s41598-017-18878-7
|View full text |Cite
|
Sign up to set email alerts
|

Neither action nor phonological video games make dyslexic children read better

Abstract: The prevalence and long-term consequences of dyslexia make it crucial to look for effective and efficient ways of its therapy. Action video games (AVG) were implied as a possible remedy for difficulties in reading in Italian and English-speaking children. However, the studies examining the effectiveness of AVG application in dyslexia suffered from significant methodological weaknesses such as small sample sizes and lack of a control group with no intervention. In our study, we tested how two forms of training:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
1
16
1
7
Order By: Relevance
“…The reading improvements after the AVG training were characterized by an improvement in reading speed, without a cost in accuracy. These results are consistent with a selective improvement in processing speed of graphene-to-phoneme mapping previously found in some AVG training studies (e.g., Gori et al, 2016;Franceschini et al, 2013Franceschini et al, , 2017aFranceschini et al, , 2017bŁuniewska et al, 2018; press in this issue; see for a discussion Vidyasagar, in press in this issue). Importantly, in Experiment 4 we confirm the crowding reduction and reading speed enhancement only in children with DD that are able to efficiently perform the AVG training, improving their game scores (Franceschini and Bertoni, in press in this issue).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reading improvements after the AVG training were characterized by an improvement in reading speed, without a cost in accuracy. These results are consistent with a selective improvement in processing speed of graphene-to-phoneme mapping previously found in some AVG training studies (e.g., Gori et al, 2016;Franceschini et al, 2013Franceschini et al, , 2017aFranceschini et al, , 2017bŁuniewska et al, 2018; press in this issue; see for a discussion Vidyasagar, in press in this issue). Importantly, in Experiment 4 we confirm the crowding reduction and reading speed enhancement only in children with DD that are able to efficiently perform the AVG training, improving their game scores (Franceschini and Bertoni, in press in this issue).…”
Section: Discussionsupporting
confidence: 91%
“…In the intervention studies, children with DD were trained with action video games (AVG), which have repeatedly shown to reduce crowding (Green and Bavelier, 2007;Franceschini et al, 2013Franceschini et al, , 2017b and improve spatial attention (see Green and Bavelier, 2012 for a review and Bediou et al, 2018 for a recent meta-analysis). AVG were also found to improve reading efficiency in individuals with DD (Franceschini et al, 2013(Franceschini et al, , 2017a(Franceschini et al, , 2017bGori et al, 2016;Łuniewska et al, 2018;see Franceschini et al, 2015 for a review) and other visual disorders (Vedamurthy et al, 2015;Gambacorta et al, 2018), possibly through the amelioration of the dorsal fronto-parietal pathway efficiency (Bavelier et al, 2012;Gori et al, 2016;Föcker et al, 2018aFöcker et al, , 2018b. Thus, in Experiment 3 and 4 we used AVG training to reduce crowding and to improve reading efficiency in two groups of unselected children with DD.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies, comparing commercial action video games to non-action video games, without a waitlist group, showed improvement in reading words and phonological decoding (58,66). Łuniewska et al examined studies which included more participants, a wait list control group, one intervention group using the same commercially available action video game and one control group using a non-action video game specifically developed by the research team to be based on phonological awareness tasks (56). Results revealed that the two game intervention groups had the same enhancement of reading skills and that the wait list control group, which did not participate in any training, presented the same enhancement of reading skills as the two training groups.…”
Section: Discussionmentioning
confidence: 99%
“…("digital games" OR "serius games" OR "video games" OR "computer games" OR gaming OR App) AND (Literacy AND "phonemic awareness" OR phonic OR "phonemic skills" OR "phonemic application") 11 trabalhos 9 trabalhos Google Acadêmico ("jog* digitais" OR "jog* eletrônicos" OR "jogos sérios" OR "digital games" OR "serius games" OR "video games" OR gaming OR App "computer games") AND (alfabetização OR letramento AND "consciência fon*" OR Literacy OR "phonemic awareness" OR phonic OR "phonemic skills" OR "phonemic application") As 10 pesquisas com modalidade experimental e abordagem quantitativa realizaram coleta de dados por meio da formação de dois grupos, um experimental (GE) e outro controle (GC) (ECALLE et al, 2009;FARIAS;COSTA;SANTOS, 2013;JAMSHIDIFARSANI et al, 2019;KARTAL;TERZIYAN, 2015;KYLE et al, 2013;RICHARDSON;LYYTINEN, 2014). Apenas uma das pesquisas utilizou três tipos de grupos: GE, GC e Grupo Controle Passivo (ŁUNIEWSKA et al, 2018).…”
Section: Web Of Scienceunclassified
“…O tempo de intervenção com os jogos digitais teve grande variação, pois tivemos períodos de tempo entre 3 e 28 horas. Do total de pesquisas experimentais, seis delas somaram de 6 a 15 horas de intervenção, durante 5 a 12 semanas (ECALLE et al, 2009;FRANCESCHINI et al, 2017;KYLE et al, 2013;ŁUNIEWSKA et al, 2018;RICHARDSON;LYYTINEN, 2014;ROSAS et al, 2017); duas pesquisas tiveram três horas de intervenção em média (FARIAS; COSTA; SANTOS, 2013; KARTAL; TERZIYAN, 2015); e apenas uma pesquisa teve uma média superior a 28 horas de intervenção, focada em múltiplas habilidades de leitura com jogos que trabalham a consciência fonológica (JAMSHIDIFARSANI et al, 2019).…”
Section: Web Of Scienceunclassified